Role of membrane redox in aging-related diseases - Morré, Dorothy M.; Morré, D. James (Acta Biologica Szegediensis, 2006)
A number of different ECTO-NOX forms have been described as being connected with aging-related diseases. The constitutive form, CNOX, serves as a terminal oxidase of plasma membrane electron transport and functions in the growth process. tNOX is present in addition to CNOX on the surface of all cancer cells and contributes to the unregulated growth characteristic of cancer cells. An age-related ECTO-NOX, arNOX, generates superoxide and may contribute to age-related generation of reactive oxygen species. ECTO-NOX proteins and prions share properties in common as do amyloid-forming proteins of various neurodegenerative disorders. A better understanding of ECTO-NOX proteins may lead to new therapeutic strategies for these several age-related disorders.